2002
DOI: 10.1007/s101440200002
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal trends in adult body size of Dolly Varden, with special reference to the food availability hypothesis

Abstract: The food availability hypothesis (FAH) predicts that the relative productivity of ocean and freshwater habitats changes with latitude, and that anadromy will evolve when ocean productivity is greater than that in neighboring freshwater habitats, or vice versa. In data sets for the anadromous salmonid species Salvelinus malma, we show that the relative body size at maturity of anadromous populations is much larger in the northern limits of their ranges than that of fluvial populations, and, conversely, that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In contrast, the probable increase in size of anadromous Dolly Varden Salvelinus malma with latitude might merely reflect latitude-dependent ocean productivity (i.e. food availability) (Maekawa and Nakano 2002). Most studies on geographic size patterns in salmonids have evaluated correlations between latitude and size (e.g.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, the probable increase in size of anadromous Dolly Varden Salvelinus malma with latitude might merely reflect latitude-dependent ocean productivity (i.e. food availability) (Maekawa and Nakano 2002). Most studies on geographic size patterns in salmonids have evaluated correlations between latitude and size (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…Salmonids are well known to exhibit geographic patterns of life history traits, such as latitudinal gradients in egg size and number (Fleming and Gross 1990;Beacham and Murray 1993;Morita et al 2009), incidence of parr maturation (Yamamoto et al 1999), age or size at smolting (L' Abée-Lund et al 1989; Machidori and Kato (1985) Metcalfe and Thorpe 1990; Jonsson and L'Abée-Lund 1993), body size of anadromous returns (Salo 1991;Maekawa and Nakano 2002;Tamate and Maekawa 2006), altitudinal variations in body size of mature male parr and threshold size for parr maturation (Baum et al 2004). It has often been concluded that these patterns could be reflections of local adaptation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additional evidence to support the FAH is based on the findings that differences in body size between anadromous and non‐anadromous Dolly Varden Salvelinus malma (Walbaum) decrease with decreasing latitude, i.e. the advantage of anadromy decreases with decreasing latitude (Maekawa & Nakano, 2002). Studies of anadromous Dolly Varden at the southern limits of their distribution, however, are limited (Maekawa, 1973; Komiyama et al ., 1982; Kishi & Maekawa, 2003).…”
Section: Means ± Sd and Ranges Of Dolly Varden Fork Lengths On The mentioning
confidence: 99%
“…They occur in North America from the Pacific Northwest, north to the Mackenzie River basin in Canada and in Far East Asia from north Siberia and neighboring islands, south to Hokkaido Island, Japan. Salvelinus malma is iteroparous and anadromous, though populations in the southern part of the range below 44°N are often freshwater resident (Maekawa and Nakano, 2002). Three allopatric subspecies of S. malma have been described: southern Asian Dolly Varden S. m. krascheninnikovi, northern Dolly Varden S. m. malma, and southern North American Dolly Varden S. m. lordi (Behnke, 1984;Dunham et al, 2008).…”
Section: Introductionmentioning
confidence: 97%